Cost of stroke in low and middle income countries: a systematic review. Issue 6 (7th July 2014) - Kaur, Paramdeep; Kwatra, Gagandeep; Kaur, Raminder; Pandian, Jeyaraj D.
<x xml:space="preserve">Abstract</x> Background There is limited information available from low and middle‐income countries regarding the cost of stroke treatment. Hence, we aimed to review the costs of stroke in low and middle‐income countries. Summary of review The literature search was done using databases: PubMed/Medline, Ovid, EconLit and Google Scholar from 1966 until January 2014 using key words 'economic impact of stroke', 'cost of illness in low and middle income countries' and 'cost of stroke'. With these key words, 10/184 articles were retained for this review. The cost data were converted to 2013 currency values using a web‐based tool (CCEMG‐EPPI‐centre cost converter). Most of the included studies were conducted in Asia. The design of these studies was retrospective and conducted predominantly in multicenter private hospitals. The highest mean direct medical cost of stroke was US 8424 in Nigeria. The lowest mean cost of stroke was in Senegal (US 416). The average length of hospital stay was longest (20 days) in China. The main predictors of higher costs appeared to be due to differences in length of stay and stroke severity. Conclusion Costs of stroke are variable because of heterogeneous healthcare systems prevailing in low and middle‐income countries. Length of hospital stay and stroke severity appear to be the main predictors of cost. Understanding the costs of stroke in low and middle‐income countries is important. However, the evidence remains limited because there is a lack of standardized research. Future research should focus on using a uniform method across low and middle‐income countries for estimating the costs of stroke.